Evidence for Involvement of the Salmonella enterica Z-Ring Assembly Factors ZapA and ZapB in Resistance to Bile - Fernández-Fernández, Rocío; Hernández, Sara B.; Puerta-Fernández, Elena; Sánchez-Romero, María A.; Urdaneta, Verónica; Casadesús, Josep (Frontiers in Microbiology, 2021)
Genes annotated as ygfE and yiiU in the genome of Salmonella enterica serovar Typhimurium encode proteins homologous to E. coli cell division factors ZapA and ZapB, respectively. ZapA– and ZapB– mutants of S. enterica are bile-sensitive. The amount of zapB mRNA increases in the presence of a sublethal concentration of sodium deoxycholate (DOC) while zapA mRNA remains unaffected. Increased zapB mRNA level in the presence of DOC is not caused by upregulation of zapB transcription but by increased stability of zapB mRNA. This increase is suppressed by an hfq mutation, suggesting the involvement of a small regulatory RNA. We provide evidence that such sRNA is MicA. The ZapB protein is degraded in the presence of sodium deoxycholate (DOC), and degradation appears to involve the Lon protease. We propose that increased stability of zapB mRNA in the presence of DOC may counter degradation of bile-damaged ZapB, thereby providing sufficient level of functional ZapB protein to permit Z-ring assembly in the presence of bile.